Analisis Kondisi Sosial Dan Kearifan Lokal Masyarakat Desa Semangat Gunung, Kecamatan Merdeka, Kabupaten Karo Tahun 2025: Penelitian - Mahara Sintong; Zulfajri; Anisa Muftih; Claudia Grace Natasya Simarmata; Friska Salsabilla; Rosa Delima Lumbantungkup; Hadriadi Iskandar Sipayung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Tourism development in Semangat Gunung Village has significantly influenced the community’s social structure and the sustainability of local wisdom. This study aims to analyze the impact of the growing accommodation sector and hot spring attractions on livelihoods, social stratification, and the preservation of cultural values. The research employed a qualitative descriptive-analytical approach using observations and interviews with tourism business actors and local residents. The findings reveal a shift in livelihoods from agriculture to tourism services, the emergence of new social groups, and increased interaction between locals and visitors. Despite these changes, several forms of local wisdom—such as mutual cooperation, traditional kerja tahun ceremonies, customary-based management of hot springs, and community security systems—remain preserved. However, tourism also presents challenges, including cultural commercialization, land disputes, rising individualism, and declining interest among youth in cultural traditions. These results highlight the need for collaboration among village authorities, customary institutions, and tourism stakeholders to ensure balanced tourism development that supports economic growth while preserving cultural identity.